Application of Genomic Sequencing to Refine Patient Stratification for Adjuvant Therapy in Renal Cell Carcinoma - Vasudev, Naveen S; Scelo, Ghislaine; Glennon, Kate I; Wilson, Michelle; Letourneau, Louis; Eveleigh, Robert; Nourbehesht, Nazanin; Arseneault, Madeleine; Paccard, Antoine; Egevad, Lars; Viksna, Juris; Celms, Edgars; et al. (Clinical cancer research, 2023)
PURPOSE: Patients with resected localized clear-cell renal cell carcinoma (ccRCC) remain at variable risk of recurrence. Incorporation of biomarkers may refine risk prediction and inform adjuvant treatment decisions. We explored the role of tumor genomics in this setting, leveraging the largest cohort to date of localized ccRCC tissues subjected to targeted gene sequencing. EXPERIMENTAL DESIGN: The somatic mutation status of 12 genes was determined in 943 ccRCC cases from a multinational cohort of patients, and associations to outcomes were examined in a Discovery (n = 469) and Validation (n = 474) framework. RESULTS: Tumors containing a von-Hippel Lindau (VHL) mutation alone were associated with significantly improved outcomes in comparison with tumors containing a VHL plus additional mutations. Within the Discovery cohort, those with VHL+0, VHL+1, VHL+2, and VHL+≥3 tumors had disease-free survival (DFS) rates of 90.8%, 80.1%, 68.2%, and 50.7% respectively, at 5 years. This trend was replicated in the Validation cohort. Notably, these genomically defined groups were independent of tumor mutational burden. Amongst patients eligible for adjuvant therapy, those with a VHL+0 tumor (29%) had a 5-year DFS rate of 79.3% and could, therefore, potentially be spared further treatment. Conversely, patients with VHL+2 and VHL+≥3 tumors (32%) had equivalent DFS rates of 45.6% and 35.3%, respectively, and should be prioritized for adjuvant therapy. CONCLUSIONS: Genomic characterization of ccRCC identified biologically distinct groups of patients with divergent relapse rates. These groups account for the ∼80% of cases with VHL mutations and could be used to personalize adjuvant treatment discussions with patients as well as inform future adjuvant trial design.
Keywords: mutace; Neoplasm Recurrence, Local; Kidney Neoplasms; nádory ledvin; Carcinoma, Renal Cell; lidé; Von Hippel-Lindau Tumor Suppressor Protein; karcinom z renálních buněk; Mutation; nádorový supresorový protein VHL; lokální recidiva nádoru; Humans